Shaping up the green entrepreneurial inclination among the university students - T. Ramayah,; Seyedeh Khadijeh Taghizadeh,; Syed Abidur Rahman, (Asian Academy of Management Journal, 2022)
Green entrepreneurship is the movement of deliberately addressing an environmental/ social problem/need through the apprehending of entrepreneurial ideas. However, becoming green entrepreneurs possess challenges which is needed through apprehending entrepreneurial ideas. Therefore, this study proposed and tested an integrative, multi- perspective framework towards green entrepreneurial inclination among university students in Malaysia. The main objective of this study is to determine the significant predictive role of a range of university support, institutional support, family support, and acquaintances support for green entrepreneurial inclination. Cross-sectional survey was directed through structured questionnaires among the university students. Partial least squares method was adopted using the SmartPLS 3.0 software to analyse the data from 1,000 respondents. The findings revealed that perceived educational, business development, institutional support along with perceived family and acquaintances supports play a significant role for green entrepreneurial inclination. The result of the study will provide guidelines to entrepreneurial universities to open up diverse opportunities for green entrepreneurial ventures. Non-governmental organisations, financial institutions, and patent organisations can also offer services to potential green entrepreneurs. This study will surely benefit all these parties to accelerate the green business and align with the “going green” movement. Originality of this research is an integrated multi-perspective framework to find support for green entrepreneurial inclination.